2013
DOI: 10.1371/journal.pone.0073618
|View full text |Cite
|
Sign up to set email alerts
|

New Structural Variants of Aeruginosin Produced by the Toxic Bloom Forming Cyanobacterium Nodularia spumigena

Abstract: Nodularia spumigena is a filamentous diazotrophic cyanobacterium that forms blooms in brackish water bodies. This cyanobacterium produces linear and cyclic peptide protease inhibitors which are thought to be part of a chemical defense against grazers. Here we show that N. spumigena produces structurally novel members of the aeruginosin family of serine protease inhibitors. Extensive chemical analyses including NMR demonstrated that the aeruginosins are comprised of an N-terminal short fatty acid chain, L-Tyr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(116 citation statements)
references
References 31 publications
4
108
0
4
Order By: Relevance
“…Spumigins (SPUs), nodularins (NPs) and APs were detected in all 25 N. spumigena strains, whereas aeruginosins were not found in seven of them (Figure S9 and Table S3). These findings agree with previous studies [21,22,23]. Production of pseudoaeruginosins NS1 ( m / z 531) and NS2 ( m / z 533) was confirmed only in six strains (CCNP1402, BY1, CCY9414, AV1, KAC71, and KAC87), indicating that in N. spumigena this class of peptides belongs to the most rare ones.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Spumigins (SPUs), nodularins (NPs) and APs were detected in all 25 N. spumigena strains, whereas aeruginosins were not found in seven of them (Figure S9 and Table S3). These findings agree with previous studies [21,22,23]. Production of pseudoaeruginosins NS1 ( m / z 531) and NS2 ( m / z 533) was confirmed only in six strains (CCNP1402, BY1, CCY9414, AV1, KAC71, and KAC87), indicating that in N. spumigena this class of peptides belongs to the most rare ones.…”
Section: Resultssupporting
confidence: 92%
“…These include 14 spumigins, 5 aeruginosins, 2 pseudoaeruginosins, 2 nodularins, and 36 anabaenopeptins (Table S2). Many of these peptides have been previously reported [7,16,20,21,22,23,25]. However, new proposed structures of 7 anabaenopeptins (APs) and one cyanopeptolin-like peptide were characterized in this study (Table S2 and Figures S1–S8).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…2S) et al 1990;Ohta et al 1994;Sano et al, 2001), serine proteases (aeruginosins, spumigins, anabaenopeptins, cyanopeptolins) (Sano & Kaya, 1995;Ishida et al, 1999;Itou et al, 1999;Murakami et al, 2000;Ploutno et al, 2002;Radau et al, 2003;Elert et al, 2005;Fewer et al, 2009Fewer et al, , 2013 and compounds cytotoxic against human cancer cell lines (nostocyclopeptides) (Golakoti et al, 2001) (Supplementary Fig. 3S).…”
Section: Resultsmentioning
confidence: 99%
“…Acid hydrolysis and amino acid analysis of Nwp W1 produced N-CH 3 -L-Phe, L-Ser, D-Ser, (2S,4S)-4-CH 3 -Pro, D-Leu, L-Ile, L-Tyr, and (2S,4R)-4-OH-Hyp. 15 N labeling showed that Nwp's contained 10 nitrogen atoms, indicating a presence of 10 amino acids. All these results together with the elemental composition data presented in Table 1 and accurate product ion masses presented in Figure 3 made it possible to draw the structures of the nostoweipeptins W1−W7 ( Figure 4).…”
Section: Acs Chemical Biologymentioning
confidence: 99%